ANALISIS SOSIAL EKONOMI CALON PETANI PERLUASAN SAWAH DI KABUPATEN TULANG BAWANG, PROVINSI LAMPUNG - Ahmad Thoriq; Desi Yunita; Budi Sutrisno; Nur Syamsiyah (Universitas Tribhuwana Tunggadewi, 2017)
Socio-economic is one of the factors that determines the feasibility of wetland expansion. Survey of socio-economic characteristics of prospective farmers is done on prospective location of rice field extension in Tulang Bawang district spread in six villages in four subdistricts. Data collection was conducted using questionnaires, and deepened with Focus Group Discussion (FGD) approaches, in-depth interviews, and field observations. The results showed that the age of prospective farmers was below 50 years old (77.02%), elementary school 31.36%, junior high 27.62% and high school 27.35%, mostly farmers (83.95%), Land of 2 hectares per farmer, and most willing to paddy (96,80%). Economically, wetland expansion program can improve farmer's welfare because the location candidate is not economically utilized swamp land, while social factor that hamper rice expansion program is land ownership conflict as happened in Andalas Village Cermin Subdistrict Rawa Pitu.